Prognostic performance of copeptin among patients with acute decompensated heart failure. Issue 8 (10th November 2021) - Ozmen, Caglar; Deveci, Onur Sinan; Tepe, Omer; Yesildas, Cuma; Ünal, İlker and Yıldız, İbrahim and Eker Akıllı, Rabia and Deniz, Ali and Demir, Mesut and Kanadaşı, Mehmet and Usal, Ayhan
Abstract: Background: In heart failure (HF), various biomarkers have been established for prognosis. However, little is known about the relevance of copeptin measurements to HF. This study aimed to explore the prognostic value of copeptin for predicting cardiovascular (CV) death or HF-related re-hospitalisation in patients with acute decompensated HF. Materials and Methods: We prospectively enrolled 155 consecutive patients with acute signs and symptoms of HF. Plasma copeptin and N-terminal pro-B-type natriuretic peptide (NT-proBNP) levels were measured at admission. Patients were monitored for 90 days regarding the composite endpoint of CV death or acute HF-related re-hospitalisation. Results: Of the 155 patients enrolled, 40 reached the endpoint, and 115 were in a stable condition during follow-up. Patients who reached an adverse endpoint showed higher NT-proBNP and copeptin levels compared to patients in stable condition. Receiver operating characteristic curve analysis revealed that the area under curve of copeptin 0.844 (95% CI, 0.753–0.935) was superior to that of NT-proBNP 0.809 (95% CI, 0.729–0.890) for the prediction of adverse events within 90 days. Meanwhile, compared to the group with lower copeptin levels (<34 pmol/L), patients with higher copeptin levels (≥34 pmol/L) were at a 10.672-times higher risk of CV death or acute HF-related re-hospitalisation. Multivariate Cox proportional hazards regression analysis revealed that increased copeptin level was a significantly independent predictor of adverse events (risk ratio, 1.051; 95% CI, 1.020–1.083; p < 0.001). Conclusion: Copeptin was found to be a strong, novel marker for predicting CV death or HF-related re-hospitalisation in patients with acute decompensated HF.